Zapuščina arhitekturne in tehnične infrastrukturne dediščine - Jankovič Potočnik, Aleksander (Urbani izziv, 2001)
In the intoduction the conceptual framework of dealing with heritage is elaborated with emphasis on the subjective dialectic pairs: natural-artificial, old-new and beatiful-ugly. These are further explained with relation to heritage and activities for its protections. By presenting successful and less successful examples of integrating, above all tehnical heritage as a spatial value, the author concludes theat such relationas towards tehnical heritage have to been taken, which can return heritage its value of utility.
Keywords: arhitekturna dediščina; Australia; Avstralija; cultural heritage; infrastructure; infrastruktura; kulturna dediščina; Slovenia; Slovenija; spomeniško varstvo; tehniška dediščina; tehniški spomeniki